Determinan Potensi Kecurangan Dana Desa di Kabupaten Pasaman - Sopya Sopya; Erly Mulyani (Universitas Negeri Padang, 2023)
This study aims to determine the effect of transparency, accountability, organizational culture, and internal control on the potential for misappropriation of village funds (Empirical Study in Pasaman District Village). The population used in this study were 37 villages in Pasaman Regency. The sampling technique used is the total sampling method, where the number of samples and the population is the same. This type of research is quantitative research. The source of data in this study is primary data by distributing questionnaires to village officials. Data analysis used multiple linear regression analysis. The results of this study indicate that accountability and internal control have a negative and significant effect on the potential for misappropriation of village funds. Meanwhile, transparency and organizational culture do not affect the potential for misappropriation of village funds.